2023
DOI: 10.3390/brainsci13040690
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Routine Laboratory Tests Predict One-Year Cognitive and Functional Decline in a Population Aged 75+ Years

Abstract: Background: Cognitive and functional decline are common problems in older adults, especially in those 75+ years old. Currently, there is no specific plasma biomarker able to predict this decline in healthy old-age people. Machine learning (ML) is a subarea of artificial intelligence (AI), which can be used to predict outcomes Aim: This study aimed to evaluate routine laboratory variables able to predict cognitive and functional impairment, using ML algorithms, in a cohort aged 75+ years, in a one-year follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The methodologies vary from traditional ML approaches to advanced deep learning models, using different types of data, including genetic data, neuroimaging data, neuropsychological assessments, and, more recently, data from wearable devices [20]. In a study published by Gomes et al [21], the potential of ML algorithms to predict cognitive and functional decline in individuals aged 75 and older using routine laboratory tests was analyzed. The study applied RF, SVM, and XGBoost algorithms, identifying 20 key laboratory variables as predictors.…”
Section: Related Workmentioning
confidence: 99%
“…The methodologies vary from traditional ML approaches to advanced deep learning models, using different types of data, including genetic data, neuroimaging data, neuropsychological assessments, and, more recently, data from wearable devices [20]. In a study published by Gomes et al [21], the potential of ML algorithms to predict cognitive and functional decline in individuals aged 75 and older using routine laboratory tests was analyzed. The study applied RF, SVM, and XGBoost algorithms, identifying 20 key laboratory variables as predictors.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies have demonstrated the potential of using routine peripheral blood parameters to predict AD risk as many parameters are altered in AD patients and some factors are associated with cognitive decline [13][14][15][16][17][18][19] . Considering the easy accessibility and cost-effectiveness of routine blood tests, routine blood analytes could complement neuropsychological tests as screening tools before conducting neuroimaging tests and detecting CSF/blood biomarkers to predict future cognitive decline in MCI subjects.…”
mentioning
confidence: 99%